Sideroblastic anemia associated with multisystem mitochondrial disorders. Issue 4 (26th December 2018) - Tesarova, Marketa; Vondrackova, Alzbeta; Stufkova, Hana; Veprekova, Lenka; Stranecky, Viktor; Berankova, Kamila; Hansikova, Hana; Magner, Martin; Galoova, Natalia; Honzik, Tomas; Vodickova, Elena; Stary, Jan; et al.
Abstract: Background: Sideroblastic anemia represents a heterogeneous group of inherited or acquired diseases with disrupted erythroblast iron utilization, ineffective erythropoiesis, and variable systemic iron overload. In a cohort of 421 patients with multisystem mitochondrial diseases, refractory anemia was found in 8 children. Results: Five children had sideroblastic anemia with increased numbers of ring sideroblasts >15%. Two of the children had a fatal course of MLASA1 syndrome (mitochondrial myopathy, lactic acidosis, and sideroblastic anemia [SA]) due to a homozygous, 6‐kb deletion in the PUS1 gene, part of the six‐member family of pseudouridine synthases (pseudouridylases). Large homozygous deletions represent a novel cause of presumed PUS1 ‐loss‐of‐function phenotype. The other three children with SA had Pearson syndrome (PS) due to mtDNA deletions of 4 to 8 kb; two of these children showed early onset of PS and died due to repeated sepsis; the other child had later onset of PS and survived as the hematological parameters normalized and the disease transitioned to Kearns–Sayre syndrome. In addition, anemia without ring sideroblasts was found in three other patients with mitochondrial disorders, including two children with later onset of PS and one child with failure to thrive, microcephaly, developmental delay, hypertrophic cardiomyopathy, and renal tubular acidosis due to the heterozygous mutations c.610A>G (p.Asn204Asp) and c.674C>T (p.Pro225Leu) in the COX10 gene encoding the cytochrome c oxidase assembly factor. Conclusions: Sideroblastic anemia was found in fewer than 1.2% of patients with multisystem mitochondrial disease, and it was usually associated with an unfavorable prognosis.